2018
DOI: 10.16931/1995-5464.2018276-83
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute pancreatitis: risk factors of adverse outcomes and their correction

Abstract: Aim. To analyze management of severe acute destructive pancreatitis and to determine the main tactical, anatomical and pathophysiological factors determining risks of adverse outcomes. Material and methods. 3581 patients with acute pancreatitis were enrolled. Retrospectively, 239 patients were assigned to severe pancreatic necrosis; invasive surgical techniques were applied in 210 cases. Twenty-nine patients with pancreatic necrosis underwent endoscopic papillosphincterotomy with main pancreatic duct stenting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…The analysis of modern literature has shown that in different periods of time such methods of improving the outflow of pancreatic secretions in acute pancreatitis as EPST, removal of the pinched stone of the BDS ampoule, dissection of the cicatricial stricture of the LPD ampoule, active aspiration of pancreatic secretions, interventions for tumor strictures in the LPD area, stenting of the main pancreatic duct with short plastic stents, nasopancreatic drainage, as well as the use of intraductal administration of various drugs were used [7][8][9]. But these methods have not been widely used in practice until today [4,7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of modern literature has shown that in different periods of time such methods of improving the outflow of pancreatic secretions in acute pancreatitis as EPST, removal of the pinched stone of the BDS ampoule, dissection of the cicatricial stricture of the LPD ampoule, active aspiration of pancreatic secretions, interventions for tumor strictures in the LPD area, stenting of the main pancreatic duct with short plastic stents, nasopancreatic drainage, as well as the use of intraductal administration of various drugs were used [7][8][9]. But these methods have not been widely used in practice until today [4,7].…”
Section: Methodsmentioning
confidence: 99%
“…We proceeded from the position that the restoration of the outflow from the preserved part of the pancreas by EIDC is an effective prevention of the progression of the pathological process in the gland itself and its transition to parapancreatic fiber. The possible prospects of this direction in the treatment of severe PN is confirmed by the fact that the effectiveness of stenting of the Virsung duct as a measure of prevention of postmanipulatory pancreatitis is proven [4,7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Пoкaзaниями к хиpуpгичecкoму вмешательству в нaчaльнoй фaзe зaбoлeвaния являютcя: острый деструктивный холецистит при остром панкреатите (ОП), а также стерильный ПН с явлениями прогрессирующего синдрома полиорганной недостаточности (ПОН), рефрактерного к адекватной интенсивной комплексной консервативной терапии, что имеет место, как правило, при отграниченных жидкостных скоплениях или при «ферментативном» перитоните. При этом основными технологическими принципами операции являются эвакуация жидкости, обеспечение полноценного дренирования [5,7,8].…”
unclassified
“…Использование этих методов нередко дает возможность выполнить адекватный объем необходимой хирургической коррекции ПН с наименьшим риском экзогенного инфицирования [8,11]. У больных со стерильным ПН с наличием свободной жидкости в брюшной полости наиболее оптимальным хирургическим доступом является лечебно-диагностическая лапароскопия, а при обнаружении в брюшной полости и/или забрюшинном пространстве отграниченных скоплений жидкости (ОСЖ), не содержащих секвестров, -пункция и дренирование под контролем ультразвукового исследования (УЗИ) [7,9,12]…”
unclassified